Strategi Penetapan Harga Yang Efektif Untuk Meningkatkan Pemasaran Produk Spaghetti Homemade: Kasus Dana Pasta - Lenti Susanna Saragih; Nadya Rahmadhani; Kezia Virginia; Daniel Martinus (Student Scientific Creativity Journal, 2023)
This article discusses the implementation of efficient pricing strategies within a marketing management framework to increase promotion of homemade spaghetti products, with a focus on the Dana Pasta case analysis. Pricing plays a crucial role in achieving success in marketing, especially in the food industry sector. By considering variables such as high quality raw materials and careful manufacturing processes, this research explores strategic approaches that can strengthen product reputation, increase competitiveness, and attract the attention of target customers. This article discusses the basic principles of pricing, evaluates a number of strategies that can be implemented in the context of homemade spaghetti, and provides practical suggestions for improving product marketing results. Through the application of the Dana Pasta case study, the aim of this article is to provide relevant and applicable guidance for culinary business people who want to achieve success through a smart pricing approach